A fluoran-based fluorescent probe via a strategy of blocking the intramolecular photoinduced electron transfer (PET) process. Issue 20 (17th May 2017) - Huang, Kun; He, Song; Zeng, Xianshun
Graphical abstract: Highlights: A fluoran-based fluorescent probe has been prepared. The probe exhibits high selectivity and sensitivity towards ClO − . The probe can be used for imaging of ClO − in living cells. Abstract: A novel fluoran-based fluorescent probe2 has been designed and synthesized by using a strategy of blocking the intramolecular photoinduced electron transfer (PET) process. The probe keeps a ring-closed spirolactone structure in aqueous buffer solution. However, the oxidation of the probe by ClO − perturbs a new equilibrium of the structural interconversion between the nonfluorescent spirolactone and the fluorescent ring-opened zwitterion, which generates a highly selective fluorescent probe for ClO − . Meanwhile, the probe is cell membrane permeable and can be utilized as fluorescent probe for imaging ClO − in living cells.